Monetary Policy Risk: Rules versus Discretion. (28th August 2021) - Backus, David K; Chernov, Mikhail; Zin, Stanley E; Zviadadze, Irina
Abstract: Long-run asset pricing restrictions in a macro term structure model identify discretionary monetary policy separately from a policy rule. We find that policy discretion is an important contributor to aggregate risk. In addition, discretionary easing coincides with good news about the macroeconomy in the form of lower inflation, higher output growth, and lower risk premiums on short-term nominal bonds. However, it also coincides with bad news about long-term financial conditions in the form of higher risk premiums on long-term nominal bonds. Shocks to the rule correlate with changes in the yield curve's level. Shocks to discretion correlate with changes in its slope.